Ungulates increase forest plant species richness to the benefit of non‐forest specialists. (11th October 2017) - Boulanger, Vincent; Dupouey, Jean‐Luc; Archaux, Frédéric; Badeau, Vincent; Baltzinger, Christophe; Chevalier, Richard; Corcket, Emmanuel; Dumas, Yann; Forgeard, Françoise; Mårell, Anders; Montpied, Pierre; Paillet, Yoan; et al.
Abstract: Large wild ungulates are a major biotic factor shaping plant communities. They influence species abundance and occurrence directly by herbivory and plant dispersal, or indirectly by modifying plant‐plant interactions and through soil disturbance. In forest ecosystems, researchers' attention has been mainly focused on deer overabundance. Far less is known about the effects on understory plant dynamics and diversity of wild ungulates where their abundance is maintained at lower levels to mitigate impacts on tree regeneration. We used vegetation data collected over 10 years on 82 pairs of exclosure (excluding ungulates) and control plots located in a nation‐wide forest monitoring network (Renecofor). We report the effects of ungulate exclusion on (i) plant species richness and ecological characteristics, (ii) and cover percentage of herbaceous and shrub layers. We also analyzed the response of these variables along gradients of ungulate abundance, based on hunting statistics, for wild boar ( Sus scrofa ), red deer ( Cervus elaphus ) and roe deer ( Capreolus capreolus ). Outside the exclosures, forest ungulates maintained higher species richness in the herbaceous layer (+15%), while the shrub layer was 17% less rich, and the plant communities became more light‐demanding. Inside the exclosures, shrub cover increased, often to the benefit of bramble ( Rubus fruticosus agg.). Ungulates tend to favour ruderal, hemerobic, epizoochorous and non‐forest species. Among plots, the magnitude of vegetation changes was proportional to deer abundance. We conclude that ungulates, through the control of the shrub layer, indirectly increase herbaceous plant species richness by increasing light reaching the ground. However, this increase is detrimental to the peculiarity of forest plant communities and contributes to a landscape‐level biotic homogenization. Even at population density levels considered to be harmless for overall plant species richness, ungulates remain a conservation issue for plant community composition. Abstract : The French forest ecosystem monitoring network (Renecofor) provided vegetation surveys resampled over 10 years, of 82 pairs of exclosure (no ungulate) and control plots. The analysis revealed that ungulates reduce the cover and richness of the shrub layers, and increase species richness of the herbaceous layer to the benefit of light‐demanding, ruderal and non‐forest species. We also show that the magnitude of vegetation changes is proportional to local deer abundances. The tremendous increase of wild ungulate populations throughout the Northern Hemisphere in the last decades has been altering not only the woody regeneration but also the diversity of herbaceous species.